Redescription and neotype designation of the Antarctic springtail Folsomotoma octooculata (Collembola: Isotomidae) - FANCIULLI, PIETRO PAOLO; LEO, CHIARA; CONVEY, PETER; FRATI, FRANCESCO; CARAPELLI, ANTONIO (Zootaxa, 2018)
The growing interest in Antarctic collembolan species has led us to re-evaluate both the morphological and molecular aspects of different species adapted to the extreme Antarctic environment. The genus Folsomotoma includes nine species mainly distributed in Antarctic and subantarctic areas and a few additionally from Australia and South America. We herein designate the neotype of Folsomotoma octooculata (Willem 1901) and redescribe its morphological characters with particular emphasis on the sensory and ordinary chaetotaxy. Furthermore, based on analyses of both our new and previously published morphological data for F. octooculata, we propose a systematic key of the species for the genus.